Improving follow-up imaging practices for patients with community-acquired pneumonia - Meirian Evans; Aazaz Rehman; Joseph Marchant; Matthew Pavitt; Rachel Buxton-Thomas (Future Healthcare Journal)
Introduction: The incidence of lung cancer in patients presenting to hospital with community-acquired pneumonia (CAP) is variably reported as 1–9.2%.1–3 The radiographic features of pneumonia and lung cancer can be similar. Therefore, in the context of lower respiratory tract symptoms, a malignancy visible on a chest X-ray may be missed.The British Thoracic Society (BTS) guidelines for the management of CAP in adults (2009) recommend that high-risk patients (aged >50 and current or ex-smokers) with consolidation on a chest X-ray should be followed up with a repeat chest X-ray 6 weeks after their initial presentation to ensure resolution of changes and to exclude an underlying malignancy.3Initial audit data in our local respiratory department showed that 41% of patients were incorrectly not followed up with repeat imaging. The main reasons for not meeting the BTS guidelines were because imaging was not arranged or because patients did not attend.The aim of this quality improvement project (QIP) was to increase the number of patients who were successfully followed up with repeat imaging. Methods: QIP methodology was utilised to design a series of interventions for this third cycle audit. These included: a patient information sheet with the date and location of the chest X-ray given to the patient upon discharge; a reminder on the doctors’ handover proforma used at the daily board round; a poster placed within the Doctors’ Office; and an update made to the standard of practice for CAP discharges within the Trust.A prospective audit cycle was conducted to analyse the number of patients discharged with a pneumonia by the respiratory team across a 2-month period through discharge code collation. These results were subsequently compared with the first cycle audit. Results: 97 patients had discharge codes for CAP. Of these, 83 had consolidation on initial chest X-ray and, therefore, met the inclusion criteria for analysis. 31 (37.3%) patients meeting the inclusion criteria were deemed unsuitable for follow-up. 11 (13.2%) of these had alternative imaging, such as CT, requested and 11 (13.2%) were excluded due to death.Of the remaining 52 patients, 47 (90.4%) had X-rays requested by the hospital and 34 (72.3%) of these attended their planned follow-up. Only 5 (6.0%) patients incorrectly did not have imaging arranged. Conclusion: Concurrent successful interventions demonstrate a significant improvement in patient care. Before this QIP, 41% of patients were incorrectly not followed up, whereas, in this third audit cycle, only 6.0% of eligible patients did not have X-rays booked on discharge. Thus, our department is now more compliant with BTS guidelines.Improved follow-up of patients with CAP with consolidation should improve the identification of patients with persistent changes on chest X-ray after 6 weeks. In line with BTS guidelines, further investigations, such as bronchoscopy, can then be considered for these patients.3 With the increasing incidence of lung cancer in the wider population, this should have a positive impact on early detection and treatment of underlying lung malignancies.